Carbon based materials for water treatment - Tan, Jan Ching Sheng (2015)
In this increasingly modernizing world, water pollution has been a worrying source of concern. It is vital that fast and efficient materials are used to resolve these worsening contamination issues. One such material would be the three-dimensional (3D) graphene. This is because it has superior properties and characteristics such as having a porous structure and high specific area which can be used to absorb dyes as part of a solution to these issues. The 3D graphene used in this experiment was firstly fabricated by a hydrothermal reaction, followed by the freeze drying process. In this study, three main things would be tested. Firstly, to test the effect on the absorption capacity when different amount of ammonium tetrathiotungstate and thioacetamide are added to graphene oxide (GO), which will then be synthesized to form 3D graphene and absorb the different commercially used dyes. The dyes used were methylene blue (MB), rhodamine B (RB), rose bengal (ROSE) and methyl orange (MO). Secondly, to investigate the effect of graphene samples on different dyes. Lastly, to determine the rate of increase in the absorption capacity of the respective dyes. However, the results observed from one of the experiments did not align with the theory on the effect of additional compound. Hence, the result of the experiment remains inconclusive. Despite the outcome of the experimental results, it has been observed that MB can be absorbed faster than the other three dyes. The data could help one to determine when to change the material if it were to be used in water treatment. Therefore, further work can be done to determine the type as well as the amount of compounds to add so as to achieve an optimal absorption capacity of materials which possess a 3D graphene network structure.